A Boy Called Bat - Arnold, Elana K.; Santoso, Charles (New York, NY : Walden Pond Press, an imprint of HarperCollinsPublishers, 2017)
When his veterinarian mom brings home a stray baby skunk that needs rehabilitation before it can be placed in a wild animal shelter, Bat, who has autism, resolves to prove that he's up to the challenge of caring for the skunk permanently.
Keywords: Autism in children -- Juvenile fiction; Skunks as pets -- Juvenile fiction; Wildlife rehabilitation -- Juvenile fiction; Autism -- Fiction; Skunks as pets -- Fiction; Wildlife rehabilitation -- Fiction; Juvenile fiction